Illicit Enrichment and Human Rights: Comparative Legal Policy in Indonesia and Poland - Ismail Marzuki; I Gede Widhiana Suarda; Fanny Tanuwijaya; Gautama Budi Arundhati (Jurnal Suara Hukum, 2026)
Corruption in Indonesia has been classified as an extraordinary crime; however, the absence of an illicit enrichment offense has resulted in law enforcement primarily targeting the symptoms of corruption rather than its root cause, namely the accumulation of disproportionate and unexplained wealth. This condition creates an urgent need to examine the potential criminalization of illicit enrichment while ensuring the protection of human rights. This study aims to analyze the construction of legal policy in Indonesia and Poland and to assess the extent to which criminal law policies concerning illicit enrichment in both jurisdictions integrate fundamental principles of criminal law and human rights within their normative design. The research employs a normative legal method, applying both comparative and conceptual approaches. The findings indicate that Indonesia remains in a transitional phase between the orientations of state efficiency and defendant’s rights, whereas Poland places greater emphasis on rights protection through the mechanism of extended confiscation. The criminalization of illicit enrichment can only be justified if it is formulated with precision and proportionality in order to maintain a fair balance between the effectiveness of anti-corruption enforcement and the protection of fundamental human rights.